Capacity and accountability in the Agricultural Extension System in Malawi: Insights from a survey of service providers in 15 districts - Ragasa, Catherine; Mzungu, Diston; Kaima, Eric; Kazembe, Cynthia; Kalagho, Kenan (International Food Policy Research Institute, 2017)
This report summarizes the data collected from a survey of government and nongovernment extension service providers (GSPs and non-GSPs, respectively) in 15 sample districts in Malawi. Together with the recently published report that looks at farmers’ perspective (Ragasa and Niu 2017), this report is aimed for use by various stakeholders in Malawi, especially in the review of the national extension policy and development of an extension strategy, and in the implementation and monitoring of extension activities under the National Agriculture Policy.